1999
DOI: 10.1098/rspb.1999.0878
|View full text |Cite
|
Sign up to set email alerts
|

Females of the grasshopper Chorthippus parallelus (Zett.) do not remate for fresh sperm

Abstract: The evolution of female multiple mating is still a largely debated ¢eld. Among the bene¢ts that have been proposed to explain this risky behaviour is the replenishment of sperm reserves. Apart from an increase in total sperm number, it can be an expression of post-copulatory mate choice or can be directed towards the uptake of fresh sperm. Using fresh sperm for fertilization instead of sperm aged by storage in the female genital tract may avoid a lowered fertilization capacity, an increase in deleterious e¡ect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 63 publications
2
32
0
1
Order By: Relevance
“…This was not tested in the present paper but it was found that matings reduced sperm numbers in future matings for at least 1 day (i.e. approximately 5% of a male's lifetime): in three populations of C. parallelus (including E and P), ejaculate sizes declined from 100 to less than 10% with one recovery day between copulations but did not decline if there were 4 days in between (K. Reinhardt 1999Reinhardt & 2002.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was not tested in the present paper but it was found that matings reduced sperm numbers in future matings for at least 1 day (i.e. approximately 5% of a male's lifetime): in three populations of C. parallelus (including E and P), ejaculate sizes declined from 100 to less than 10% with one recovery day between copulations but did not decline if there were 4 days in between (K. Reinhardt 1999Reinhardt & 2002.…”
Section: Resultsmentioning
confidence: 99%
“…I used an established sperm count protocol (Reinhardt et al 1999;Reinhardt 2001) to measure ejaculate size. Potential manipulations of sperm by females did not affect the results because the entire spermathecal tract was removed from the female within 30 min of copulation.…”
Section: Methodsmentioning
confidence: 99%
“…The quantity and quality of stored sperms are constraints acting on female fecundity. Arguments summarized by Reinhardt et al (1999), advocate that a decrease in sperm quality and quantity occurs with sperm age, resulting in a decrease in probabilities of fertilization and hence in female fitness. The increase in progeny sex ratio with increasing age of parents may result from several factors operating at a time.…”
Section: Subsequent Days Of Ovipositionmentioning
confidence: 98%
“…One female collected from the field, was mated three weeks later and examined in the laboratory one week after she mated. Sperm counts were done using a modified version of the method used by Reinhardt et al (1999). Briefly, the female was dissected and her spermatheca removed, placed in 0.2 ml of locust saline and slightly ruptured.…”
Section: Mating Effort and Sperm Numbermentioning
confidence: 99%